2015
DOI: 10.1111/asj.12355
|View full text |Cite
|
Sign up to set email alerts
|

Effect of active immunization against GnRHI on the reproductive function in cat

Abstract: This study was designed to explore the effect of active immunization against maltose binding protein-gonadotropin releasing hormone I hexamer (MBP-GnRH-I6) on the reproductive function in cats. Each immunized cat was administered twice intramuscularly in the neck at 16 and 20 weeks old. The concentrations of the testosterone and estradiol and the level of anti-GnRH-I antibody in the serum were measured by radioimmunoassay and ELISA, respectively. The results showed that the weight and size of testicles and ova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In addition to its endocrine effects, GnRH influences the morphological aspects of animal growth and development. Jiang et al observed seminal tubular hypoplasia and reduced spermatogonial differentiation in immunised mice, confirming the profound morphological impact of GnRH-targeted immunisation [3]. Similarly, chitosan-adjuvant GnRH vaccines are associated with testicular atrophy and the onset of azoospermia, suggesting their effectiveness in inducing sterility [17].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition to its endocrine effects, GnRH influences the morphological aspects of animal growth and development. Jiang et al observed seminal tubular hypoplasia and reduced spermatogonial differentiation in immunised mice, confirming the profound morphological impact of GnRH-targeted immunisation [3]. Similarly, chitosan-adjuvant GnRH vaccines are associated with testicular atrophy and the onset of azoospermia, suggesting their effectiveness in inducing sterility [17].…”
Section: Introductionmentioning
confidence: 92%
“…This approach relies on vaccination against the gonadotropin-releasing hormone (GnRH) to inhibit reproductive functions [ 1 , 2 ]. GnRH, a pivotal neuropeptide synthesised and secreted by the hypothalamus [ 3 ], plays a central role in regulating the reproductive axis. Structurally, GnRH is a decapeptide with a specific sequence that is pyroglutamylated and amidated at its terminus, conferring enhanced biological activity and stability [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tissues collected from the rats were fixed in 4% paraformaldehyde for 12 ~24 h at 4 °C, then were processed and stained with hematoxylin-eosin (HE) as Jiang et al described (41) The morphological changes and tissue structure of testis, thymus and spleen were observed under light microscope (BX51). Images were taken with Nikon Digital Sight DS-SMC camera.…”
Section: Morphological Observation Of Tissue Samplesmentioning
confidence: 99%
“…GnRH vaccines have also shown success in female cats, inducing infertility for at least 20 months after two injections in one study, and for 5 months to 5 years after one injection in another study . A recombinant GnRH‐I maltose binding protein vaccine showed promising results in both male and female cats, although mating trials need to be performed . GnRH vaccines have also shown success in both male and female domestic horses, without any serious adverse effects …”
Section: Gnrh Vaccinementioning
confidence: 99%